Titanium carbide coated zinc hydroxystannate hybrid powder and preparation method and application thereof
By coating zinc hydroxystannate with dopamine and combining with two-dimensional titanium carbide, a hybrid titanium carbide coated zinc hydroxystannate was prepared, which solved the compatibility and dispersion of ZHS in ABS, and achieved effective flame retardant, smoke suppression and mechanical properties of ABS were improved.
Patent Information
- Application Number
- CN202310144792.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-02-21
AI Technical Summary
In the prior art, the use of zinc hydroxystannate (ZHS) in ABS has problems such as poor compatibility, poor dispersion, and the inability to effectively improve the dual performance of flame retardant and smoke suppression in a single addition.
Titanium carbide coated zinc hydroxystannate hybrid powder (Ti3C2Tx@PDA@ZHS) was prepared by coating zinc hydroxystannate with dopamine and combining with two-dimensional titanium carbide through interface charge attraction. This material has a cube structure with rounded edges, improving the dispersion and compatibility of ZHS in polymers.
It significantly reduces the smoke generation rate and smoke density of ABS resin, and reduces the release of toxic gases such as HCN, NOx, and CO, and improves the mechanical properties of the composite materials.
Smart Images

Figure CN116534891B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, in particular to a titanium carbide-coated zinc hydroxystannate hybrid powder and a preparation method and application thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) resin is one of the most widely used engineering plastics with excellent impact resistance, heat resistance, low temperature resistance, chemical resistance and electrical properties. ABS is one of the most widely used engineering plastics in machinery, automobile, electrical, electronic, instrumentation, textile and construction industries. However, ABS is highly flammable and will form highly toxic HCN and NOx gases during combustion, produce a large amount of black smoke, reduce visibility, and make it impossible for people to escape, which limits the further use of ABS. To expand the scope of use of ABS, it is necessary to improve the flame retardant properties of ABS and suppress the black smoke and toxic gases produced during combustion.
[0003] At present, there are many research works on improving the flame retardant properties of polymers. Dispersing some nano-hybrid materials into polymers to improve the performance of polymer materials is the most common method. There are many types of smoke suppressants reported so far, such as zinc borate, zinc hydroxystannate, magnesium hydroxide, ferrocene, talc, dimethyl silicone, etc. Chinese patent CN202011607902 reported that fluoroboron fluoride-modified titanium carbide BODIPY-Ti3C2Tx can increase the oxygen index of ABS, reduce the heat release rate and smoke generation rate during combustion, and inhibit the release of toxic gases such as HCN, NOx, NH3, and CO. At low addition amounts, it can also increase the tensile strength of ABS and maintain its elongation at break, showing good mechanical properties. Chinese patent CN201910801724 reports low-smoke halogen-free flame-retardant ABS material for edge banding and its preparation method. The low-smoke halogen-free flame-retardant ABS material for edge banding includes the following raw materials: ABS resin, halogen-free flame-retardant filler, smoke suppressant, surface modifier and lubricant. The halogen-free flame-retardant filler and smoke suppressant have good compatibility with ABS resin, which not only improves the flame retardant and smoke suppression effect of ABS material, but also strengthens ABS material. Chinese patent CN201610911349 discloses low smoke density ABS resin and its preparation method. It uses aluminum hydroxide as a smoke suppression flame retardant, has a lower smoke density, can more effectively reduce the smoke release of the material in a fire, and provide better protection for the safety of people in a fire.
[0004] Zinc hydroxystannate (ZHS) is a flame retardant and smoke suppression nanomaterial commonly used in polymers because its Zn and Sn elements can form corresponding metal oxides attached to the polymer surface during combustion to achieve a catalytic smoke suppression effect. As a good choice for flame retardancy and smoke suppression, ZHS is widely used in flame and smoke suppression of polymers such as polyvinyl chloride and epoxy resin. However, there are few reports on the use of ZHS in ABS. There is no research on the compatibility issue between ZHS and ABS. In addition, the sharp cubic shape of ZHS leads to poor dispersibility and compatibility when added to polymers, which further reduces the mechanical properties of the material. In addition, unmodified ZHS is more likely to agglomerate, which further reduces the dispersibility of ZHS in polymers. Finally, the addition of a single ZHS cannot achieve the improvement of the dual flame retardant and smoke suppression properties of ABS. Therefore, the preparation of highly dispersed ZHS nanoparticles for flame retardancy, smoke suppression and toxicity reduction of ABS is a current research and development difficulty. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an independently packaged endoscope film bag, which can solve the problem that the sharp cubic shape of the existing ZHS leads to poor dispersibility and compatibility when added to polymers, which will further reduce the mechanical properties of the material; the unmodified ZHS is more likely to agglomerate, which further reduces the dispersibility of ZHS in polymers.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] The present invention is achieved through the following technical solutions:
[0008] Titanium carbide coated zinc hydroxystannate hybrid powder, including
[0009] The titanium carbide-coated hydroxy zinc stannate hybrid powder is formed by combining dopamine-coated hydroxy zinc stannate and two-dimensional titanium carbide through interface charge attraction. The titanium carbide-coated hydroxy zinc stannate hybrid powder is Ti3C2Tx@PDA@ZHS; the titanium carbide-coated hydroxy zinc stannate hybrid powder has a cubic structure with rounded edges.
[0010] Application of titanium carbide coated zinc hydroxystannate hybrid powder as flame retardant, smoke suppressant and toxicity reducing agent for ABS.
[0011] Furthermore, titanium carbide-coated zinc hydroxystannate hybrid powder is mixed with ABS in liquid phase to obtain a composite material, in which the addition ratio of titanium carbide-coated zinc hydroxystannate hybrid powder in the composite material is 2% by mass.
[0012] A method for preparing titanium carbide-coated zinc hydroxystannate hybrid powder, the preparation method comprising the following steps:
[0013] S1. Etching the aluminum atomic layer in aluminum titanium carbide using a mixed solution of lithium fluoride and hydrochloric acid to prepare titanium carbide precipitate;
[0014] S2, the titanium carbide precipitate obtained in S1 is redispersed in water, ultrasonicated and centrifuged, the precipitate is removed, and the supernatant is taken to obtain titanium carbide nanosheets (Ti3C2T x ) suspension;
[0015] S3, using zinc sulfate and sodium stannate as raw materials to synthesize zinc hydroxystannate, and then dissolving zinc hydroxystannate powder and dopamine together with stirring to obtain dopamine-coated zinc hydroxystannate (PDA@ZHS);
[0016] S4, dissolving the zinc hydroxystannate obtained in S3 in deionized water, and adjusting the pH value to 1-3 to obtain an acidic solution;
[0017] S5, adding the hydroxy zinc stannate solution obtained in S4 to the titanium carbide nanosheet suspension obtained in S2, and the nano powder precipitate obtained after the reaction is titanium carbide coated hydroxy zinc stannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0018] Furthermore, the mass ratio of the dopamine to the titanium carbide precipitate is 1:(0.5-1).
[0019] The preparation method of titanium carbide coated zinc hydroxystannate hybrid powder comprises the following steps:
[0020] S1. Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10-15mL of 7-10mol / L hydrochloric acid, stir and react at 35-50°C for 36-60h, and the stirring speed is 400-600rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and dry to obtain titanium carbide precipitate;
[0021] S2, taking 0.2 g of the titanium carbide precipitate obtained in S1, dispersing it in 50 mL of deionized water, ultrasonicating it at 0-5°C for 30-60 min with an ultrasonic power of 100-300 W, then centrifuging it at 4000-5000 rpm, removing the precipitate, and taking the supernatant to obtain a titanium carbide nanosheet suspension;
[0022] S3, 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O were dispersed in 300mL of deionized water and stirred for 4h, the lower precipitate was centrifuged and dried in an oven at 60℃ to obtain a white powder as pure ZHS; then 0.5g of pure ZHS was uniformly dispersed in 100ml Tris-HCl solution (10mmol, pH=8.5) by ultrasonication, 0.2g of dopamine was dissolved in a small amount of Tris-HCl solution, and it was slowly added to the ZHS solution with a dropper, and stirred at room temperature for 24-48h to obtain a dark brown solution; finally, the obtained liquid was centrifuged to remove the lower precipitate, washed with water at least 4 times, and dried at 60℃ to obtain a brown powder as PDA@ZHS;
[0023] S4. Dissolve the PDA@ZHS powder in a small amount of deionized water, add HCl solution to adjust the pH to acidic, take the titanium carbide suspension, add the acidified PDA@ZHS solution to the titanium carbide suspension, and precipitate can be seen in the solution, indicating that PDA@ZHS is successfully attached to the titanium carbide nanosheets. Then centrifuge to remove the lower precipitate, wash with water to neutrality, and freeze-dry to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0024] Furthermore, the HCl solution is added dropwise to adjust the pH to 1-3, and a titanium carbide suspension is prepared according to a mass ratio of PDA@ZHS to titanium carbide of 1:1.
[0025] Compared with the prior art, the beneficial effects of the present invention include:
[0026] The invented titanium carbide-coated hydroxyzinc stannate hybrid powder is formed by combining hydroxyzinc stannate and two-dimensional titanium carbide through interface charge attraction. Compared with covalent bond bonding, it will not destroy the surface structure of the nanomaterial and can maintain the original morphology and structure of titanium carbide nanosheets and hydroxyzinc stannate.
[0027] The titanium carbide-coated zinc hydroxystannate hybrid powder of the present invention significantly improves the sharp characteristics of the surface of the zinc hydroxystannate, enhances the dispersibility of the nanomaterial in the polymer, and enhances the mechanical properties of the composite material.
[0028] The titanium carbide-coated zinc hydroxystannate hybrid powder of the present invention, thanks to the synergistic flame retardant effect of titanium carbide and ZHS, significantly reduces the smoke generation rate and smoke density of ABS resin, and reduces the release of toxic gases such as HCN, NOx, and CO. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The disclosure of the present invention is described with reference to the accompanying drawings. It should be understood that the drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. Among them:
[0030] Figure 1 This is a scanning electron microscope (SEM) image of the ZHS prepared in Example 1.
[0031] Figure 2 ZHS (ac), PDA@ZHS (be) and Ti3C2T prepared in Example 1 x Transmission electron microscopy (TEM) image of @PDA@ZHS (cf).
[0032] Figure 3 ZHS, PDA@ZHS, Ti3C2T prepared in Example 1 x 、Ti3C2T x X-ray diffraction (XRD) pattern of @PDA@ZHS.
[0033] Figure 4 ZHS, PDA@ZHS, Ti3C2T prepared in Example 1 x 、PDA、Ti3C2T x Thermal gravimetric loss curve (TGA) of @PDA@ZHS.
[0034] Figure 5 Curves of heat release rate (a), total heat release rate (b), CO release curve (c) and CO2 release curve (d) of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3.
[0035] Figure 6 The curves of different toxic gas release concentrations of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3 over time: (a) HCN, (b) NO, (c) NO2, (d) HCHO.
[0036] Figure 7 The light transmittance (a) and smoke density (b) of the pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3 are curves showing changes over time. DETAILED DESCRIPTION
[0037] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes and drawings are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0038] The present invention provides a titanium carbide-coated hydroxy zinc stannate hybrid powder, which is a titanium carbide-coated hydroxy zinc stannate hybrid powder (Ti3C2T x@PDA@ZHS), the titanium carbide-coated zinc hydroxystannate hybrid powder has a cubic structure with rounded edges.
[0039] The invention provides an application of titanium carbide coated hydroxy zinc stannate hybrid powder as an ABS flame retardant, smoke suppressant and toxicity reducing agent, wherein the titanium carbide coated hydroxy zinc stannate hybrid powder is mixed with ABS in liquid phase to obtain a composite material, wherein the addition ratio of the titanium carbide coated hydroxy zinc stannate hybrid powder in the composite material is 2% by mass.
[0040] Specifically, the steps of preparing the composite material by liquid phase mixing are:
[0041] S1, 0.4g titanium carbide coated zinc hydroxystannate hybrid powder (Ti3C2Tx@PDA@ZHS) and 19.6g ABS (acrylonitrile-butadiene-styrene copolymer) resin were dissolved in 200-250mL N, N-dimethylformamide, stirred and ultrasonically mixed for 50-60min;
[0042] S2. The uniformly mixed ABS and Ti3C2Tx@PDA@ZHS mixed solution is slowly added into deionized water, and the mixture is repeatedly washed with deionized water and dried to obtain the ABS / Ti3C2Tx@PDA@ZHS nanocomposite material.
[0043] The method for preparing the titanium carbide-coated zinc hydroxystannate hybrid powder of the present invention comprises:
[0044] First, ZHS (zinc hydroxystannate) was modified with dopamine, and the aluminum layer was selectively etched out from carbon-aluminum-titanium to prepare titanium carbide. Finally, the interface charge attraction between titanium carbide and dopamine was used to prepare titanium carbide-coated zinc hydroxystannate hybrid powder.
[0045] The specific preparation method comprises the following steps:
[0046] S1. Etching the aluminum atomic layer in aluminum titanium carbide using a mixed solution of lithium fluoride and hydrochloric acid to prepare titanium carbide precipitate;
[0047] S2, the titanium carbide precipitate obtained in S1 is redispersed in water, ultrasonicated and centrifuged, the precipitate is removed, and the supernatant is taken to obtain titanium carbide nanosheets (Ti3C2T x ) suspension;
[0048] S3, using zinc sulfate and sodium stannate as raw materials to synthesize zinc hydroxystannate, and then dissolving zinc hydroxystannate powder and dopamine together with stirring to obtain dopamine-coated zinc hydroxystannate (PDA@ZHS);
[0049] S4, dissolving the zinc hydroxystannate obtained in S3 in deionized water, and adjusting the pH value to 1-3 to obtain an acidic solution;
[0050] S5, adding the hydroxy zinc stannate solution obtained in S4 to the titanium carbide nanosheet suspension obtained in S2, and the nano powder precipitate obtained after the reaction is the titanium carbide coated hydroxy zinc stannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0051] Example 1
[0052] 1) Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10mL of 10mol / L hydrochloric acid, stir and react at 40°C for 48h, and the stirring speed is 400rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and then dry to obtain titanium carbide precipitate.
[0053] 2) 0.2 g of the titanium carbide precipitate obtained in step 1) was dispersed in 50 mL of deionized water, ultrasonicated at 0° C. for 30 min with an ultrasonic power of 300 W, and then centrifuged at 5000 rpm to remove the precipitate and take the supernatant to obtain a titanium carbide nanosheet suspension.
[0054] 3) Disperse 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O in 300ml of deionized water and stir for 4h, centrifuge to remove the lower precipitate, and dry it in an oven at 60℃ to obtain a white powder as pure ZHS; then ultrasonically disperse the obtained 0.5g of pure ZHS in 100ml of Tris-HCl solution (10mmol, pH=8.5), dissolve 0.2g of PDA (dopamine) in a small amount of Tris-HCl (trishydroxymethylaminomethane hydrochloride) solution, slowly add it to the ZHS solution with a dropper, stir at room temperature for 24h, and obtain a dark brown solution. Finally, centrifuge the obtained liquid to remove the lower precipitate, wash it with water at least 4 times, and dry it at 60℃ to obtain a brown powder as PDA@ZHS.
[0055] 4) PDA@ZHS powder was dissolved in a small amount of deionized water, and HCl solution was added to adjust the pH to 1. x (titanium carbide) mass ratio is 1:1; take Ti3C2T x The acidified PDA@ZHS solution was added dropwise to the Ti3C2T x In the solution, precipitates can be seen in the solution, indicating that PDA@ZHS is successfully loaded on Ti3C2T x The nanosheets are then centrifuged to remove the lower precipitate, washed with water until neutral, and freeze-dried to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0056] Figure 1The SEM image of ZHS prepared in Example 1; Figure 1 It can be seen that the morphology of ZHS is a cubic structure with sharp edges and corners, and the size is about 100-200nm.
[0057] Figure 2 ZHS, PDA@ZHS and Ti3C2T prepared in Example 1 x TEM (transmission electron microscope) image of @PDA@ZHS; Figure 2 It can be seen that PDA and Ti3C2T x The surface coating significantly improves the sharpness of the ZHS edge, indicating that the use of PDA and Ti3C2T x Coating can effectively improve the edge sharpness of ZHS and enhance its compatibility with the polymer matrix.
[0058] Figure 3 ZHS, PDA@ZHS, Ti3C2T prepared in Example 1 x 、Ti3C2T x XRD pattern of @PDA@ZHS; from Figure 3 It can be seen that the characteristic diffraction peaks of ZHS are in good agreement with the cubic phase of its standard crystal structure (JCPDS: NO.74-1825), indicating that the purity of ZHS prepared in Example 1 is very high; the characteristic diffraction peaks of PDA@ZHS are not significantly different from those of pure ZHS. x The XRD spectrum of @PDA@ZHS shows a characteristic diffraction peak (200) similar to that of pure ZHS at around 2θ≈22.5°, while pure Ti3C2T x The XRD spectrum of Ti3C2T x Successful preparation of @PDA@ZHS hybrid powder.
[0059] Figure 4 ZHS, PDA@ZHS, Ti3C2T prepared in Example 1 x 、PDA、Ti3C2T x @PDA@ZHS TGA curve diagram; from Figure 4 It can be seen that ZHS presents a one-step thermal decomposition process, and the thermal stability of ZHS decreases to a certain extent after being wrapped by PDA, and there is a continuous thermal weight loss, indicating that the carbon-forming performance of PDA is poor and it will continue to decompose during the thermal decomposition process; pure Ti3C2T x The thermal stability is good, and no obvious thermal weight loss can be seen during the heating process. x The thermal gravimetric curve of @PDA@ZHS is between ZHS and Ti3C2T x between, indicating that Ti3C2Tx The preparation of @PDA@ZHS hybrid powders was successful.
[0060] Example 2
[0061] 1) Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10mL of 10mol / L hydrochloric acid, stir and react at 40°C for 48h, and the stirring speed is 400rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and then dry to obtain titanium carbide precipitate.
[0062] 2) 0.2 g of the titanium carbide precipitate obtained in step 1) was dispersed in 50 mL of deionized water, ultrasonicated at 0° C. for 30 min with an ultrasonic power of 300 W, and then centrifuged at 5000 rpm to remove the precipitate and take the supernatant to obtain a titanium carbide nanosheet suspension.
[0063] 3) Disperse 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O in 300ml of deionized water and stir for 4h, centrifuge to remove the lower precipitate, and dry it in an oven at 60℃ to obtain a white powder as pure ZHS. Then, ultrasonically disperse the obtained 0.5g of pure ZHS in 100ml of Tris-HCl solution (10mmol, pH=8.5), dissolve 0.2g of PDA in a small amount of Tris-HCl solution, slowly add it to the ZHS solution with a dropper, stir at room temperature for 48h, and obtain a dark brown solution. Finally, centrifuge the obtained liquid to remove the lower precipitate, wash it with water at least 4 times, and dry it at 60℃ to obtain a brown powder as PDA@ZHS.
[0064] 4) PDA@ZHS powder was dissolved in a small amount of deionized water, and HCl solution was added to adjust the pH to 1. x The mass ratio is 1:1 to take Ti3C2T x The acidified PDA@ZHS solution was added dropwise to the Ti3C2T x In the solution, precipitates can be seen in the solution, indicating that PDA@ZHS is successfully loaded on Ti3C2T x The nanosheets are then centrifuged to remove the lower precipitate, washed with water until neutral, and freeze-dried to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0065] Example 3
[0066] 1) Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10mL of 10mol / L hydrochloric acid, stir and react at 40°C for 48h, and the stirring speed is 400rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and then dry to obtain titanium carbide precipitate.
[0067] 2) 0.2 g of the titanium carbide precipitate obtained in step 1) was dispersed in 50 mL of deionized water, ultrasonicated at 0° C. for 30 min with an ultrasonic power of 300 W, and then centrifuged at 5000 rpm to remove the precipitate and take the supernatant to obtain a titanium carbide nanosheet suspension.
[0068] 3) Disperse 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O in 300ml of deionized water and stir for 4h, centrifuge to remove the lower precipitate, and dry it in an oven at 60℃ to obtain a white powder as pure ZHS. Then, ultrasonically disperse the obtained 0.5g of pure ZHS in 100ml of Tris-HCl solution (10mmol, pH=8.5), dissolve 0.2g of PDA in a small amount of Tris-HCl solution, slowly add it to the ZHS solution with a dropper, stir at room temperature for 24h, and obtain a dark brown solution. Finally, centrifuge the obtained liquid to remove the lower precipitate, wash it with water at least 4 times, and dry it at 60℃ to obtain a brown powder as PDA@ZHS.
[0069] 4) PDA@ZHS powder was dissolved in a small amount of deionized water, and HCl solution was added to adjust the pH to 2. PDA@ZHS and Ti3C2T x The mass ratio is 1:1 to take Ti3C2T x The acidified PDA@ZHS solution was added dropwise to the Ti3C2T x In the solution, precipitates can be seen in the solution, indicating that PDA@ZHS is successfully loaded on Ti3C2T x The nanosheets are then centrifuged to remove the lower precipitate, washed with water until neutral, and freeze-dried to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0070] Example 4
[0071] 1) Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10mL of 10mol / L hydrochloric acid, stir and react at 40°C for 48h, and the stirring speed is 400rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and then dry to obtain titanium carbide precipitate.
[0072] 2) 0.2 g of the titanium carbide precipitate obtained in step 1) was dispersed in 50 mL of deionized water, ultrasonicated at 0° C. for 30 min with an ultrasonic power of 300 W, and then centrifuged at 5000 rpm to remove the precipitate and take the supernatant to obtain a titanium carbide nanosheet suspension.
[0073] 3) Disperse 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O in 300ml of deionized water and stir for 4h, centrifuge to remove the lower precipitate, and dry it in an oven at 60℃ to obtain a white powder as pure ZHS. Then, ultrasonically disperse the obtained 0.5g of pure ZHS in 100ml of Tris-HCl solution (10mmol, pH=8.5), dissolve 0.2g of PDA in a small amount of Tris-HCl solution, slowly add it to the ZHS solution with a dropper, stir at room temperature for 24h, and obtain a dark brown solution. Finally, centrifuge the obtained liquid to remove the lower precipitate, wash it with water at least 4 times, and dry it at 60℃ to obtain a brown powder as PDA@ZHS.
[0074] 4) PDA@ZHS powder was dissolved in a small amount of deionized water, and HCl solution was added to adjust the pH to 3. PDA@ZHS and Ti3C2T x The mass ratio is 1:1 to take Ti3C2T x The acidified PDA@ZHS solution was added dropwise to the Ti3C2T x In the solution, precipitates can be seen in the solution, indicating that PDA@ZHS is successfully loaded on Ti3C2T x The nanosheets are then centrifuged to remove the lower precipitate, washed with water until neutral, and freeze-dried to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder (Ti3C2T x @PDA@ZHS).
[0075] Example 5
[0076] Take 0.4g titanium carbide coated zinc hydroxystannate nanopowder (Ti3C2T x @PDA@ZHS) and 19.6 g ABS were dissolved in 200 mL N, N-dimethylformamide, stirred and ultrasonically mixed for 50 min, and the mixed ABS and Ti3C2T x The mixed solution of @PDA@ZHS was slowly added into deionized water, washed repeatedly with deionized water, and dried to obtain ABS / Ti3C2T x @PDA@ZHS nanocomposite, Ti3C2T x The mass percentage of @PDA@ZHS in the composite material is 2%.
[0077] Comparative Example 1
[0078] 0.4 g of zinc hydroxystannate nanopowder (ZHS) and 19.6 g of ABS were dissolved in 200 mL of N,N-dimethylformamide, stirred and ultrasonically mixed for 50 min, and the uniformly mixed ABS and ZHS mixed solution was slowly added to deionized water. After repeated washing with deionized water and drying, an ABS / ZHS nanocomposite material was obtained, and the mass percentage of ZHS in the composite material was 2%.
[0079] Comparative Example 2
[0080] 0.4 g dopamine-coated zinc hydroxystannate nanopowder (PDA@ZHS) and 19.6 g ABS were dissolved in 200 mL N,N-dimethylformamide, stirred and ultrasonically mixed for 50 min, and the uniformly mixed ABS and PDA@ZHS mixed solution was slowly added to deionized water. After repeated washing with deionized water and drying, an ABS / PDA@ZHS nanocomposite material was obtained, and the mass percentage of PDA@ZHS in the composite material was 2%.
[0081] Comparative Example 3
[0082] Take 0.4 titanium carbide nanopowder (Ti3C2T x ) and 19.6 g ABS were dissolved in 200 mL N, N-dimethylformamide, stirred and ultrasonically mixed for 50 min, and the mixed ABS and Ti3C2T x The mixed solution was slowly added into deionized water, washed repeatedly with deionized water, and dried to obtain ABS / Ti3C2T x Nanocomposite materials, Ti3C2T x The mass percentage in the composite material is 2%.
[0083] Figure 5 The heat release rate (a), total heat release rate (b), smoke generation rate (c) and total smoke release (d) curves of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3. Table 1 (as shown in Table 1 below) is a comparison of the ignition time (TTI), peak heat release rate (PHRR), total heat release (THR), peak CO2 generation rate (PCO2P), peak CO generation rate (PCOP) and limiting oxygen index (LOI) data of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3. Figure 5 As can be seen from Table 1, the PHRR formed by pure ABS during combustion is 1062.9kW / m 2 The PHRRs of ABS / ZHS and ABS / PDA@ZHS are 1046.8 and 1101.3kW / m 2 , indicating that the addition of ZHS and PDA@ZHS has no significant effect on the thermal release of ABS.x The PHRR is reduced to 904.1kW / m 2 , and the introduction of Ti3C2T x After @PDA@ZHS, PHRR is further reduced (877.1kW / m 2 ), which decreased by about 17.5%. The decrease in PHRR value may be due to the x The nanosheets acted as a barrier during the combustion process, blocking the decrease in PHRR value, which may be due to the Ti3C2T x The nanosheets acted as a barrier to heat release during combustion. For total heat release (THR), there was no significant difference between the two composites, which may be due to the relatively low addition amount. In addition, CO and CO2 release during combustion were also effectively suppressed. The PCOP of pure ABS was 0.028 g / s, and that of ABS / Ti3C2T x The PCOP of @PDA@ZHS is 0.023g / s, a decrease of about 17.9%. The PCO2P of pure ABS is 0.77g / s, and the PCO2P of ABS / Ti3C2T x The PCO2P of @PDA@ZHS is 0.65g / s, a decrease of about 15.6%. This is mainly due to the x The oxidation of ZHS produces ZnO and SnO, which block the release of CO and CO2, while transition metal carbides (Ti3C2T x ) plays a catalytic conversion role internally, thereby reducing the release of CO and CO2.
[0084] Table 1: Data comparison diagram of Example 5 and Comparative Examples 1-3
[0085]
[0086]
[0087] Figure 6 The concentration change curves of different toxic gases released from pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3 over time: (a) HCN, (b) NO, (c) NO2, (d) HCHO. Figure 6 It can be seen that the peak concentration of HCN released by pure ABS during combustion is about 116.4ppm, while after adding nanomaterials, the HCN release concentration of all ABS composites is reduced, especially ABS / Ti3C2T x@PDA@ZHS, the peak concentration of HCN was reduced to 76.7ppm, a decrease of 34.1%. In addition, under the same combustion conditions, pure ABS would release a peak concentration of 518.5ppm NO and 11.0ppm NO2, while adding Ti3C2T x After the addition of @PDA@ZHS, the release of NO and NO2 decreased to 419.8ppm and 8.8ppm, with a decrease of 19.0% and 20.0%, respectively, and both were lower than that of ABS / Ti3C2T x In the curve of HCHO concentration changing with time ( Figure 6 d), ABS / Ti3C2T x @PDA@ZHS also has a lower peak value. The above results show that ZHS and Ti3C2T x There is a synergistic effect between them, which effectively inhibits the release of toxic gases during the combustion process of ABS.
[0088] Figure 7 The light transmittance (a) and smoke density (b) of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3 change with time. Figure 7 As shown in a, the transmittance of ABS decreases earlier than that of the corresponding composites. At 500 s, the transmittance of ABS is only 0.4%. After adding ZHS and PDA@ZHS, the transmittance of ABS decreases to varying degrees. However, after adding Ti3C2T x After, ABS / Ti3C2T x @PDA@ZHS has a light transmittance of 4.0% (higher than ABS / Ti3C2T x This shows that ZHS and Ti3C2T x The smoke suppression performance of ABS is improved through synergistic effects. Figure 7 In b, the smoke density of ABS reaches 525.6 at 1200s. ABS / Ti3C2T x The smoke density of @PDA@ZHS reaches 426.7 at 1200s, which is lower than that of ABS / Ti3C2T x , ABS / PDA@ZHS and ABS / ZHS. Compared with ABS, the smoke density is reduced by 18.8%, indicating that ABS / Ti3C2T x The smoke production of @PDA@ZHS during combustion was significantly reduced. This further shows that ZHS and Ti3C2T x There is a good synergistic effect between them, which can improve the smoke suppression performance of ABS.
[0089] Therefore, according to the above results, Ti3C2T x@PDA@ZHS is an excellent flame retardant and smoke suppression material. It also helps to suppress the release of toxic gases produced by polymer materials during combustion, and can better protect people's lives and property safety when a fire occurs.
[0090] Table 2 is a comparison of the tensile properties of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3. It can be seen from Table 2 that the tensile strength of the composite material increased from 37.4MPa of pure ABS to 40.7MPa, but the strain decreased from 22.8% of pure ABS to 15.5%. This is because, on the one hand, the sharp edges of ZHS produce a large number of gaps between ABS and the sharp edges of ZHS, resulting in increased brittleness of ABS; on the other hand, the unmodified ZHS particles will agglomerate, making the dispersion of ZHS in ABS worse, resulting in a decrease in material performance. After PDA@ZHS was added to ABS, the elongation at break rose to 25.8%. This is because the modification of PDA improved the sharp edges of ZHS, improved its dispersibility in ABS, and eliminated the resulting voids. Adding Ti3C2T x After that, the stress and strain of ABS decreased significantly, which is due to the x The agglomeration of nanosheets in ABS leads to the degradation of the mechanical properties of the composites. x After @PDA@ZHS, the mechanical properties are significantly improved, with a tensile strength of 39.2 MPa and an elongation at break of 26.3%, which are not significantly different from those of pure ABS. This may be due to the Ti3C2T x After compounding with PDA@ZHS, Ti3C2T x The surface functional groups, such as hydroxyl and carboxyl, form intermolecular forces with the ABS molecular chains, thereby improving the strength and toughness of the composite material.
[0091] Table 2: Comparison of tensile properties of pure ABS and its composite materials prepared in Example 5 and Comparative Examples 1-3
[0092] sample Tensile strength(MPa) Elongation at break (%) ABS 37.4±4.1 22.8±3.9 ABS / ZHS 40.7±2.6 15.5±1.3 <![CDATA[ABS / Ti3C2T x ]]> 32.0±2.6 13.3±0.5 ABS / PDA@ZHS 34.5±1.6 25.8±3.2 <![CDATA[ABS / Ti3C2T x @PDA@ZHS]]> 39.2±1.0 26.3±4.0
[0093] Combining the above combustion performance and tensile performance tests, it is not difficult to see that the two-step modified ZHS can not only better exert the flame retardant and smoke suppression performance, but also solve the problem of affecting the mechanical properties of polymers. x @PDA@ZHS hybrid powder can also be compounded with a variety of flame retardants and applied to flame retardant, smoke suppression and toxicity reduction treatment of polymer materials such as polyolefins, polyurethanes, polyamides, cyclic resins, and various thermoplastics and thermosetting plastics, and has broad market application prospects.
[0094] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A titanium carbide-coated zinc hydroxystannate hybrid powder, characterized in that: include The titanium carbide-coated hydroxy zinc stannate hybrid powder is formed by combining the dopamine-coated hydroxy zinc stannate and the two-dimensional titanium carbide through the interface charge attraction. The titanium carbide-coated hydroxy zinc stannate hybrid powder is Ti3C2T x @PDA@ZHS; The titanium carbide-coated zinc hydroxystannate hybrid powder has a cubic structure with rounded edges.
2. The method for preparing a titanium carbide-coated zinc hydroxystannate hybrid powder according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Etching the aluminum atomic layer in aluminum titanium carbide using a mixed solution of lithium fluoride and hydrochloric acid to prepare titanium carbide precipitate; S2, re-dispersing the titanium carbide precipitate obtained in S1 in water, performing ultrasonication and centrifugation, removing the precipitate, and taking the supernatant to obtain a titanium carbide nanosheet suspension; S3, using zinc sulfate and sodium stannate as raw materials to synthesize hydroxy zinc stannate, and then dissolving and stirring the hydroxy zinc stannate powder and dopamine to obtain dopamine-coated hydroxy zinc stannate, wherein the dopamine-coated hydroxy zinc stannate is PDA@ZHS; the mass ratio of the dopamine to the titanium carbide precipitate is 1:(0.5-1); S4, dissolving the zinc hydroxystannate obtained in S3 in deionized water, and adjusting the pH value to 1-3 to obtain an acidic solution; S5. Add the hydroxy zinc stannate solution obtained in S4 to the titanium carbide nanosheet suspension obtained in S2. The nano powder precipitate obtained after the reaction is titanium carbide-coated hydroxy zinc stannate hybrid powder.
3. The method for preparing a titanium carbide-coated zinc hydroxystannate hybrid powder according to claim 2, characterized in that: The steps include: S1. Take 0.5g of carbon aluminum titanium and 0.5g of lithium fluoride and place them in a plastic beaker, add 10-15mL of 7-10mol / L hydrochloric acid, stir and react at 35-50°C for 36-60h, and the stirring speed is 400-600rpm. After the reaction is completed, centrifuge and wash repeatedly until the pH is 7, and dry to obtain titanium carbide precipitate; S2, taking 0.2 g of the titanium carbide precipitate obtained in S1, dispersing it in 50 mL of deionized water, ultrasonicating it at 0-5°C for 30-60 min with an ultrasonic power of 100-300 W, then centrifuging it at 4000-5000 rpm, removing the precipitate, and taking the supernatant to obtain a titanium carbide nanosheet suspension; S3, 0.6g of ZnSO4·7H2O and 0.6g of Na2SnO6·3H2O were dispersed in 300mL of deionized water and stirred for 4h, the lower precipitate was centrifuged and dried in an oven at 60℃ to obtain a white powder as pure ZHS; then 0.5g of pure ZHS was uniformly dispersed in 100ml of Tris-HCl solution by ultrasonication, 0.2g of dopamine was dissolved in a small amount of Tris-HCl solution, and the solution was slowly added to the ZHS solution with a dropper, and stirred at room temperature for 24-48h to obtain a dark brown solution; finally, the liquid was centrifuged to remove the lower precipitate, washed with water at least 4 times, and dried at 60℃ to obtain a brown powder as PDA@ZHS; S4. Dissolve the PDA@ZHS powder in a small amount of deionized water, add HCl solution to adjust the pH to acidic, take the titanium carbide suspension, and add the acidified PDA@ZHS solution to the titanium carbide suspension. A precipitate can be seen in the solution, indicating that PDA@ZHS is successfully attached to the titanium carbide nanosheets. Then, centrifuge to remove the lower precipitate, wash with water to neutrality, and freeze-dry to obtain a black solid, which is the titanium carbide-coated zinc hydroxystannate hybrid powder.
4. The method for preparing a titanium carbide-coated hydroxy-zinc hybrid powder according to claim 3, characterized in that: The HCl solution is added dropwise to adjust the pH to 1-3, and a titanium carbide suspension is prepared according to a mass ratio of PDA@ZHS to titanium carbide of 1:
1.
5. The use of the titanium carbide-coated hydroxy zinc stannate hybrid powder according to claim 1 as an ABS flame retardant, smoke suppressant and toxicity reducing agent; the titanium carbide-coated hydroxy zinc stannate hybrid powder is mixed with ABS in liquid phase to obtain a composite material, wherein the addition ratio of the titanium carbide-coated hydroxy zinc stannate hybrid powder in the composite material is 2% by mass.
Citation Information
Patent Citations
ABS resin with low smoke density and preparation method thereof
CN106496920A
Low-smoke halogen-free flame-retardant ABS material for edge sealing strips, and preparation method thereof
CN110437577A
Titanium carbide nanopowder for flame retardancy, smoke suppression and toxicity reduction of ABS and its preparation method
CN112724462B
Magnesium hydroxide coated zinc hydroxystannate powder and preparation method thereof
CN106006721A
Titanium carbide nano-powder for flame retardance, smoke suppression and toxicity reduction of ABS and preparation method of titanium carbide nano-powder
CN112724462A